2020
DOI: 10.1007/s00787-020-01682-6
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between child mental health need and professional service utilisation: Examining the influence of mothers’ parental attributions on professional help-seeking intentions

Abstract: There is a significant gap between the need for child mental health services and use of these services by families. Parental attributions may play a role in this. This study examined whether mothers’ attributions about their child’s problems influence professional help-seeking intentions in a general sample of community mothers. Secondary analysis re-examined this hypothesis in a subgroup of mothers of children with clinically elevated mental health symptoms. Cross-sectional survey data were collected from mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
1
2
0
1
Order By: Relevance
“…The results showed that a mother's help-seeking behavior has a significant effect on her adolescents' helpseeking behaviors, independently of other variables. These findings are consistent with previous studies that highlight the importance of evaluating and intervening with parents, particularly mothers, when working with adolescents with suicidal thoughts [56][57][58]. A systematic review of 14 studies also found a significant association between mothers' helpseeking and their offspring's help-seeking behaviors [59].…”
Section: The Adolescent's Help-seeking Facilitated By the Mother's He...supporting
confidence: 91%
“…The results showed that a mother's help-seeking behavior has a significant effect on her adolescents' helpseeking behaviors, independently of other variables. These findings are consistent with previous studies that highlight the importance of evaluating and intervening with parents, particularly mothers, when working with adolescents with suicidal thoughts [56][57][58]. A systematic review of 14 studies also found a significant association between mothers' helpseeking and their offspring's help-seeking behaviors [59].…”
Section: The Adolescent's Help-seeking Facilitated By the Mother's He...supporting
confidence: 91%
“…Family factors had a limited focus in research. Parents play a role in professional help seeking for mental health problems of their children ( 26 ). The perception of family regarding help seeking, psychiatric history, and better health literacy was significantly associated with the help-seeking intention ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also did not assess health beliefs which could influence intentions to use DMHIs [14]. This was done because the current study was focused on examining the moderating role of actual rather than perceived mental health need [42]. However, future research could examine putative interactions between health beliefs and technology acceptance in influencing motivations to use DMHIs.…”
Section: Discussionmentioning
confidence: 99%